2, 5-furandicarboxylic acid and synthesis method thereof
The catalytic oxidation of 2,5-furandiformaldehyde through supported metal catalysts solves the complex problems of HMF isomerization and separation, and achieves efficient and economical synthesis of 2,5-furandiformalic acid, which is suitable for industrial production.
Patent Information
- Application Number
- CN202310839146.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-10
AI Technical Summary
In the existing production methods of 2,5-furandicarboxylic acid, HMF is easily isomerized into by-products, the separation process is complicated, and there are limitations of engineering amplification.
Using a supported metal catalyst, including active components such as cobalt, copper, ruthenium, iron, etc., the reaction of oxidation of 2,5-furandiformaldehyde in an oxidation atmosphere is obtained to obtain 2,5-furandiformalic acid, which avoids the isomerization of HMF. , and simplifies the separation process.
It achieves efficient and economical synthesis of 2,5-furandicarboxylic acid, avoids the generation of by-products, improves the yield and purity of the product, and is suitable for industrial production.
Smart Images

Figure CN119306688A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic synthesis, and in particular to 2,5-furandicarboxylic acid and a synthesis method thereof. Background Art
[0002] 2,5-Furandicarboxylic acid is soluble in water under alkaline conditions and is a white powdery solid in acidic conditions. It is a white crystal or powder. It is a renewable dibasic acid monomer with an aromatic structure. It is used to prepare various alkyl-substituted or ester furan derivatives, and is used to synthesize chiral catalysts, molecular recognition receptors and polymer materials.
[0003] At present, the most common production method of 2,5-furandicarboxylic acid (FDCA) is to oxidize 2-methoxyfurfural (HMF); cellulose is hydrolyzed to obtain glucose, isomerized to obtain fructose, and fructose can be dehydrated to obtain HMF, which can be oxidized to obtain FDCA. This is the current main research direction.
[0004] Chinese patent CN106795130 B discloses a method for converting hydroxymethylfurfural into a furanic product including 2,5-furandicarboxylic acid, the method comprising combining a certain amount of hydroxymethylfurfural with water to provide an aqueous solution containing at least about five weight percent of hydroxymethylfurfural, and combining the aqueous solution with an oxygen source in the presence of a heterogeneous ruthenium-based catalyst and under conditions effective for oxidizing hydroxymethylfurfural to furanic oxidation products including 2,5-furandicarboxylic acid, but in the substantial absence of any solvent for either hydroxymethylfurfural or 2,5-furandicarboxylic acid other than water.
[0005] At present, in the process of HMF oxidation to prepare FDCA, there are disadvantages that the raw material HMF is easily isomerized into other by-products and the separation process is complicated, which has certain limitations in engineering scale-up. Summary of the invention
[0006] In view of the above situation, the present invention provides a 2,5-furandicarboxylic acid and a synthesis method thereof, wherein a supported metal catalyst is used to catalyze and oxidize 2,5-furandicarboxaldehyde to synthesize a 2,5-furandicarboxylic acid compound. The synthesis route has the characteristics of high economy and high raw material abundance, can avoid the isomerization of the raw material HMF into other by-products, and the separation process is simple.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a method for synthesizing 2,5-furandicarboxylic acid, comprising the following steps:
[0008] In the presence of a catalyst, a mixture of 2,5-furandicarboxaldehyde and a solvent reacts in an oxidizing atmosphere to obtain a reaction product containing 2,5-furandicarboxylic acid;
[0009] The catalyst comprises a carrier and an active component; the mass percentages of the carrier and the active component in the catalyst are respectively: 90% to 95% of the carrier and 5% to 10% of the active component.
[0010] According to some embodiments of the present invention, the carrier is at least one of activated carbon, alumina, and 4A molecular sieve, and the active component is at least one of cobalt, copper, ruthenium, and iron. The active component in the catalyst of the present invention mainly exists in the form of oxides.
[0011] According to some embodiments of the present invention, the solvent is selected from at least one of water and a mixture of methanol and water; preferably, the volume ratio of methanol to water in the mixture of methanol and water is (1:5) to (1:10), for example 1:8.
[0012] According to some embodiments of the present invention, the oxidizing atmosphere is air or oxygen.
[0013] According to some embodiments of the present invention, the mass ratio of 2,5-furandicarboxaldehyde to catalyst is (1-6):(0.1-0.3), for example, 1:0.1, 6:0.17, 3:0.18, 3:0.13, 3:0.14, 3:0.15.
[0014] According to some embodiments of the present invention, the ratio of 2,5-furandicarboxaldehyde to solvent is (1-6) mol:1L, for example, 1 mol:1L, 3 mol:1L, 6 mol:1L.
[0015] According to some embodiments of the present invention, the reaction conditions include: reaction temperature of 60°C to 90°C, for example, 60°C, 75°C, 90°C, reaction time of 3h to 6h, for example, 3h, 6h, stirring rate of 500r / min to 600r / min, for example, 500r / min, 600r / min.
[0016] According to some embodiments of the present invention, the synthesis method further comprises the step of filtering the reaction product; specifically, the product solution is filtered using a filtering device, the solid product is collected, and the solid product is washed with deionized water.
[0017] According to some embodiments of the present invention, the method for preparing the catalyst includes the step of using a carrier to load the active component; preferably, when using a carrier to load the active component, a metal salt solution of the active component is mixed with the carrier, dried, and then calcined in an inactive atmosphere to obtain the catalyst.
[0018] According to some embodiments of the present invention, the specific surface area of the catalyst is 300 m 3 / g~500m 3 / g, particle size is 40μm~90μm.
[0019] According to some embodiments of the present invention, the mass ratio of the metal salt of the active component to the carrier in the metal salt solution of the active component is (3-20): (20-25), for example 3.2:20, 4.1:20, 4.8:22, 15.3:25, 16.8:20, 19.7:20, 16.1:20, 15.3:20, 17.8:20; preferably, the mass concentration of the metal salt solution of the active component is 10%-20%, preferably 15%; more preferably, the metal salt solution of the active component is at least one of copper nitrate solution, iron nitrate solution, ruthenium nitrate solution and cobalt nitrate solution.
[0020] According to some embodiments of the present invention, the mixing conditions include: a stirring rate of 500 r / min to 700 r / min, for example 600 r / min, a mixing time of 1 h to 3 h, for example 2 h, and a mixing temperature of 20° C. to 30° C., for example 20° C.
[0021] According to some embodiments of the present invention, the mixing further includes a step of static sedimentation; preferably, the static sedimentation time is 2 hours.
[0022] According to some embodiments of the present invention, the drying conditions include: a temperature of 110° C. to 150° C., such as 120° C., and a time of 2 h to 3 h, such as 2 h.
[0023] According to some embodiments of the present invention, the inert atmosphere is at least one of nitrogen and argon.
[0024] According to some embodiments of the present invention, the calcination conditions include: a temperature of 250° C. to 400° C., such as 300° C., and a time of 4 h to 5 h, such as 4 h.
[0025] In the present invention, the synthetic route for synthesizing 2,5-furandicarboxylic acid is:
[0026]
[0027] This route uses a highly efficient and stable supported metal catalyst in an atmosphere of air or oxygen. In the supported metal catalyst, the metal active component is preferably at least one of cobalt, copper, ruthenium and iron. These metal components are superior to other metals in the experimental screening process.
[0028] The second aspect of the present invention provides 2,5-furandicarboxylic acid obtained by the above synthesis method.
[0029] Beneficial effects:
[0030] The invention develops a synthesis route of 2,5-furandicarboxylic acid, uses 2,5-furandicarboxaldehyde as a raw material in the synthesis process, has high atom economy, ensures that the production process is environmentally friendly, and at the same time, the catalyst used in the reaction has high catalytic efficiency and good stability, can avoid the isomerization of the raw material HMF into other by-products, and has a high total product yield.
[0031] The catalyst preparation method of the present invention is simple, convenient for large-scale preparation, and can be used in industrial production devices such as fixed fluidized beds and reactors;
[0032] The synthesis process of 2,5-furandicarboxylic acid of the present invention is an oxidation reaction, in which air or oxygen is used to oxidize the aldehyde group to a carboxyl group, and the process does not require the participation of other complex oxidizing additives; and the reaction conditions are simple, the operation is convenient, the reaction raw materials are easily available, and the product is easily extracted, and the process has potential industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a SEM photograph of the cobalt / activated carbon catalyst prepared in Example 1 of the present invention.
[0034] Figure 2 This is a SEM photograph of the cobalt / activated carbon catalyst prepared in Example 2 of the present invention.
[0035] Figure 3 This is a SEM photograph of the cobalt / activated carbon catalyst prepared in Example 3 of the present invention.
[0036] Figure 4 This is the 1H-NMR characterization of 2,5-furandicarboxylic acid prepared in Example 1 of the present invention.
[0037] Figure 5 This is the 13C-NMR characterization of 2,5-furandicarboxylic acid prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the embodiments, but the present invention is not limited by these embodiments.
[0039] The reactor used in the present invention is a common type of reactor on the market, and its operating temperature range is 10° C. to 350° C., such as a reactor with a stirrer.
[0040] The drying oven used in the present invention was purchased from Tianjin Zhonghuan Experimental Electric Furnace Co., Ltd., model ZK-38C.
[0041] The muffle furnace used in the present invention was purchased from Tianjin Zhonghuan Experimental Electric Furnace Co., Ltd., and the model number is SX-G36123.
[0042] The SEM photograph of the catalyst in the present invention is taken by a scanning electron microscope, the model of the scanning electron microscope is Quattro, and the manufacturer is FER.
[0043] The carbon spectrum / hydrogen spectrum characterization of 2,5-furandicarboxylic acid in the present invention is obtained by a nuclear magnetic resonance instrument, and the manufacturer of the nuclear magnetic resonance instrument Agilent ProPulse is Agilent.
[0044] The activated carbon in the present invention was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 98%.
[0045] The 4A molecular sieve in the present invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and has a pore size of 0.55 nm to 0.7 nm.
[0046] The aluminum oxide in the present invention is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a purity of 99.9%.
[0047] The 2,5-furandicarboxaldehyde in the present invention is purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 99%.
[0048] The purity of 2,5-furandicarboxylic acid in the present invention is determined by high performance liquid chromatography, using acetonitrile and water as mobile phases, a flow rate of 3 ml / min, and a UV detector.
[0049] The yield of 2,5-furandicarboxylic acid in the present invention is calculated by the molar mass of the product (2,5-furandicarboxylic acid) / the molar mass of the raw material (2,5-furandicarboxaldehyde).
[0050] Example 1
[0051] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0052]
[0053] (1) Catalyst preparation
[0054] 3.2 g of cobalt nitrate hexahydrate and water were mixed into a solution with a mass concentration of 15%, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a cobalt / activated carbon catalyst. The mass fraction of cobalt in the cobalt / activated carbon catalyst was 8%. The SEM photograph of the cobalt / activated carbon catalyst is shown in FIG. Figure 1 The specific surface area of the catalyst is 320m 3 / g, and the average particle size of the catalyst is 60μm.
[0055] (2) Synthesis of 2,5-furandicarboxylic acid
[0056] 124 g (1 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 1 mol / L 2,5-furandicarboxaldehyde solution, and then 12.5 g of the above-mentioned cobalt / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred at a rate of 500 r / min for reaction, wherein the reactor was connected to the outside air, the reaction temperature was set to 60° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 149.7 g, the purity of the 2,5-furandicarboxylic acid product was 98.1%, and the yield was 96.0%;
[0057] The carbon / hydrogen spectrum characterization of 2,5-furandicarboxylic acid is shown above. Figure 4 and Figure 5 , Figure 4 The carbon spectrum of 2,5-furandicarboxylic acid is characterized as 1 H-NMR (500MHz, CDCl3) δ12.56(s,2H), 7.48(s,2H), 2.90(s,1H), Figure 5 The hydrogen spectrum of 2,5-furandicarboxylic acid is characterized as 13 C-NMR (101MHz, CDCl3) δ171.3, 139.2, 130.3, 27.7.
[0058] Example 2
[0059] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0060]
[0061] (1) Catalyst preparation
[0062] 4.1 g of copper nitrate hexahydrate and water were mixed into a solution with a mass concentration of 15%, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a copper / activated carbon catalyst. The mass fraction of copper in the copper / activated carbon catalyst was 10%. The SEM photograph of the copper / activated carbon catalyst is shown in FIG. Figure 2 The specific surface area of the catalyst is 350m 3 / g, and the average particle size of the catalyst is 70μm.
[0063] (2) Synthesis of 2,5-furandicarboxylic acid
[0064] 744.3 g (6 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 6 mol / L 2,5-furandicarboxaldehyde solution, and then 21.3 g of the above copper / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred at a rate of 500 r / min for reaction, wherein the reactor was connected to the outside air, the reaction temperature was set to 90° C., and the reaction was stopped after 3 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 879.8 g, the purity of 2,5-furandicarboxylic acid was 98.0%, and the yield was 94.0%.
[0065] Example 3
[0066] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0067]
[0068] (1) Catalyst preparation
[0069] 4.8 g of ferric nitrate hexahydrate was mixed with water to prepare a solution with a mass concentration of 15%, and then 22 g of 4A molecular sieve (pore size 0.55 nm to 0.7 nm) was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to mix evenly. After standing and settling for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain an iron / activated carbon catalyst. The mass fraction of iron in the iron / activated carbon catalyst was 8%. The SEM photograph of the iron / activated carbon catalyst is shown in FIG. Figure 3 The specific surface area of the catalyst is 400m 3 / g, and the average particle size of the catalyst is 80μm.
[0070] (2) Synthesis of 2,5-furandicarboxylic acid
[0071] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 22.5 g of the above-mentioned iron / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 500 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 75° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 457.3 g, the purity of 2,5-furandicarboxylic acid was 98.0%, and the yield was 97.7%.
[0072] Example 4
[0073] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0074]
[0075] (1) Preparation of catalyst
[0076] 15.3 g of ruthenium nitrate hexahydrate and water were mixed into a solution with a mass concentration of 15%, and then 25 g of aluminum oxide was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. The dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a ruthenium / activated carbon catalyst. The mass fraction of ruthenium in the ruthenium / aluminum oxide catalyst was 5%, and the specific surface area of the catalyst was 380 m 3 / g, and the average particle size of the catalyst is 45μm.
[0077] (2) Synthesis of 2,5-furandicarboxylic acid
[0078] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 15.6 g of the above-mentioned ruthenium / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 500 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 75° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 461.7 g, the purity of 2,5-furandicarboxylic acid was 98%, and the yield was 98.7%.
[0079] Example 5
[0080] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0081]
[0082] (1) Preparation of catalyst
[0083] 8.3 g of ruthenium nitrate hexahydrate and 8.5 g of ferric nitrate hexahydrate were prepared into a solution with a mass concentration of 15% with water, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a ruthenium-iron / activated carbon catalyst, wherein the mass fraction of ruthenium in the ruthenium-iron / activated carbon catalyst was 10%, the mass fraction of iron was 5%, and the specific surface area of the catalyst was 450 m 3 / g, and the average particle size of the catalyst is 62μm.
[0084] (2) Synthesis of 2,5-furandicarboxylic acid
[0085] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 16.8 g of the above-mentioned ruthenium-iron / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 600 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 75° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 453.8 g, the purity of 2,5-furandicarboxylic acid was 98%, and the yield was 97.0%.
[0086] Example 6
[0087] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0088]
[0089] (1) Preparation of catalyst
[0090] 10.2 g of ruthenium nitrate hexahydrate and 9.5 g of copper nitrate hexahydrate were mixed with water to prepare a solution with a mass concentration of 15%, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a ruthenium-copper / activated carbon catalyst, wherein the mass fraction of ruthenium in the ruthenium-copper / activated carbon catalyst was 8%, the mass fraction of copper was 7%, and the specific surface area of the catalyst was 400 m 3 / g, and the average particle size of the catalyst is 53μm.
[0091] (2) Synthesis of 2,5-furandicarboxylic acid
[0092] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 15.6 g of the above-mentioned ruthenium-copper activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 600 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 75° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 448.8 g, the purity of 2,5-furandicarboxylic acid was 98%, and the yield was 95.9%.
[0093] Example 7
[0094] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0095]
[0096] (1) Preparation of catalyst
[0097] 8.3 g of ruthenium nitrate hexahydrate and 7.8 g of cobalt nitrate hexahydrate were prepared with water into a solution with a mass concentration of 15%, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a ruthenium-cobalt / activated carbon catalyst. The mass fraction of ruthenium in the ruthenium-cobalt / activated carbon catalyst was 7.9%, the mass fraction of cobalt was 6.5%, and the specific surface area of the catalyst was 460 m 3 / g, and the average particle size of the catalyst is 86μm.
[0098] (2) Synthesis of 2,5-furandicarboxylic acid
[0099] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 15.6 g of the above-mentioned ruthenium-cobalt / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 500 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 75° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 445.1 g, the purity of 2,5-furandicarboxylic acid was 98%, and the yield was 95.1%.
[0100] Example 8
[0101] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0102]
[0103] (1) Preparation of catalyst
[0104] 7.8 g of ferric nitrate hexahydrate and 7.5 g of copper nitrate hexahydrate were mixed with water to prepare a solution with a mass concentration of 15%, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. The dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain an iron-copper / activated carbon catalyst, wherein the mass fraction of iron in the iron-copper / activated carbon catalyst was 6.5%, the mass fraction of copper was 7.2%, and the specific surface area of the catalyst was 390 m 3 / g, and the average particle size of the catalyst is 49μm.
[0105] (2) Synthesis of 2,5-furandicarboxylic acid
[0106] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 18.6 g of the above-mentioned iron-copper / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 600 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 75° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 451.1 g, the purity of 2,5-furandicarboxylic acid was 98%, and the yield was 96.4%.
[0107] Example 9
[0108] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0109]
[0110] (1) Preparation of catalyst
[0111] 9.3 g of cobalt nitrate hexahydrate and 8.5 g of copper nitrate hexahydrate are mixed with water to prepare a solution with a mass concentration of 15%, and then 20 g of activated carbon is added to the solution. At a temperature of 20° C., the mixture is stirred at a rate of 600 r / min for 2 hours to be evenly mixed. After being allowed to settle for 2 hours, the turbid liquid is placed in a drying oven and dried at a temperature of 120° C. for 2 hours. Finally, the dried solid is calcined in a muffle furnace at a temperature of 300° C. for 4 hours in a nitrogen atmosphere to obtain a cobalt-copper / activated carbon catalyst, wherein the mass fraction of cobalt in the cobalt-copper / activated carbon catalyst is 6.3%, the mass fraction of copper is 7.4%, and the specific surface area of the catalyst is 430 m 3 / g, and the average particle size of the catalyst is 56μm.
[0112] (2) Synthesis of 2,5-furandicarboxylic acid
[0113] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 16.2 g of the above-mentioned cobalt-copper / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 500 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 75° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 453.0 g, the purity of 2,5-furandicarboxylic acid was 98%, and the yield was 96.8%.
[0114] Example 10
[0115] This embodiment provides a method for synthesizing 2,5-furandicarboxylic acid.
[0116]
[0117] (1) Preparation of catalyst
[0118] 8.3 g of ferric nitrate hexahydrate and 7.8 g of cobalt nitrate hexahydrate were prepared with water into a solution with a mass concentration of 15%, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain an iron-cobalt / activated carbon catalyst, wherein the mass fraction of iron in the iron-cobalt / activated carbon catalyst was 7.3%, the mass fraction of cobalt was 6.8%, and the specific surface area of the catalyst was 460 m 3 / g, and the average particle size of the catalyst is 77μm.
[0119] (2) Synthesis of 2,5-furandicarboxylic acid
[0120] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 15.6 g of the above-mentioned iron-cobalt / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 600 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 75° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 444.1 g, the purity of 2,5-furandicarboxylic acid was 98%, and the yield was 94.9%.
[0121] Comparative Example 1
[0122] This comparative example provides a method for synthesizing 2,5-furandicarboxylic acid.
[0123]
[0124] (1) Preparation of catalyst
[0125] 1.6 g of cobalt nitrate hexahydrate and water are prepared into a solution with a mass concentration of 15%, and then 20 g of activated carbon is added to the solution. At a temperature of 20° C., the mixture is stirred at a rate of 600 r / min for 2 hours to be evenly mixed. After being allowed to settle for 2 hours, the turbid liquid is placed in a drying oven and dried at a temperature of 120° C. for 2 hours. Finally, the dried solid is calcined in a muffle furnace at a temperature of 300° C. for 4 hours in a nitrogen atmosphere to obtain a cobalt / activated carbon catalyst. The mass fraction of cobalt in the cobalt / activated carbon catalyst is 4%, and the specific surface area of the catalyst is 320 m 3 / g, and the average particle size of the catalyst is 60μm.
[0126] (2) Synthesis of 2,5-furandicarboxylic acid
[0127] 124 g (1 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 1 mol / L 2,5-furandicarboxaldehyde solution, and then 12.5 g of the above-mentioned cobalt / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 500 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 60° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 123.7 g, the purity of the 2,5-furandicarboxylic acid product was 82.1%, and the yield was 79.3%.
[0128] Comparative Example 2
[0129] This comparative example provides a method for synthesizing 2,5-furandicarboxylic acid.
[0130]
[0131] (1) Preparation of catalyst
[0132] 9.6 g of cobalt nitrate hexahydrate and water are prepared into a solution with a mass concentration of 15%, and then 20 g of activated carbon is added to the solution. The mixture is stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid is placed in a drying oven and dried for 2 h at a temperature of 120° C. Finally, the dried solid is calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a cobalt / activated carbon catalyst, wherein the mass fraction of cobalt in the cobalt / activated carbon catalyst is 24%, and the specific surface area of the catalyst is 300 m 3 / g, and the average particle size of the catalyst is 44μm.
[0133] (2) Synthesis of 2,5-furandicarboxylic acid
[0134] 375.6 g (3 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 3 mol / L 2,5-furandicarboxaldehyde solution, and then 12.5 g of the above-mentioned cobalt / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 500 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 60° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 409.9 g, the purity of 2,5-furandicarboxylic acid was 89.4%, and the yield was about 87.6%.
[0135] Comparative Example 3
[0136] This comparative example provides a method for synthesizing 2,5-furandicarboxylic acid.
[0137]
[0138] (1) Preparation of catalyst
[0139] 3.2 g of cobalt nitrate hexahydrate and water were mixed into a solution with a mass concentration of 15%, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a cobalt / activated carbon catalyst. The mass fraction of cobalt in the cobalt / activated carbon catalyst was 8%, and the specific surface area of the catalyst was 320 m 3 / g, and the average particle size of the catalyst is 60μm.
[0140] (2) Synthesis of 2,5-furandicarboxylic acid
[0141] 124 g (1 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 1 mol / L 2,5-furandicarboxaldehyde solution, and then 12.5 g of the above-mentioned cobalt / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 400 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 60° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a total of 146.9 g of a white product 2,5-furandicarboxylic acid, the purity of the 2,5-furandicarboxylic acid product was 95.1%, and the yield was 94.2%; it can be seen that the stirring rate during the reaction was reduced, and the contact interface between the reactant and the catalyst was reduced during the reaction, which affected the yield.
[0142] Comparative Example 4
[0143] This comparative example provides a method for synthesizing 2,5-furandicarboxylic acid.
[0144]
[0145] (1) Preparation of catalyst
[0146] 3.2 g of cobalt nitrate hexahydrate and water were mixed into a solution with a mass concentration of 15%, and then 20 g of activated carbon was added to the solution. The mixture was stirred at a rate of 600 r / min for 2 h at a temperature of 20° C. to be evenly mixed. After being allowed to settle for 2 h, the turbid liquid was placed in a drying oven and dried at a temperature of 120° C. for 2 h. Finally, the dried solid was calcined in a muffle furnace at a temperature of 300° C. for 4 h in a nitrogen atmosphere to obtain a cobalt / activated carbon catalyst. The mass fraction of cobalt in the cobalt / activated carbon catalyst was 8%, and the specific surface area of the catalyst was 320 m 3 / g, and the average particle size of the catalyst is 60μm.
[0147] (2) Synthesis of 2,5-furandicarboxylic acid
[0148] 124 g (1 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 1 mol / L 2,5-furandicarboxaldehyde solution, and then 12.5 g of the above-mentioned cobalt / activated carbon catalyst was added, the reactor power was turned on, and the materials were stirred and reacted at a rate of 500 r / min, wherein the reactor was connected to the outside air, the reaction temperature was set to 20° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 101.5 g, the purity of the 2,5-furandicarboxylic acid product was 64.3%, and the yield was 65.1%; it can be seen that too low a reaction temperature during the reaction affects the yield and purity.
[0149] Comparative Example 5
[0150] This comparative example provides a method for synthesizing 2,5-furandicarboxylic acid.
[0151] 124 g (1 mol) of 2,5-furandicarboxaldehyde was added to 1 L of aqueous solution to prepare a 1 mol / L 2,5-furandicarboxaldehyde solution, the reactor power was turned on, and the materials were stirred at a rate of 500 r / min for reaction, wherein the reactor was connected to the outside air, the reaction temperature was set to 60° C., and the reaction was stopped after 6 hours; after the reaction product was cooled to 25° C., the reaction liquid was filtered to obtain a white product 2,5-furandicarboxylic acid 33.3 g, the purity of the 2,5-furandicarboxylic acid product was 31.6%, and the yield was 21.3%.
[0152] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for synthesizing 2,5-furandicarboxylic acid, characterized in that: The steps include: In the presence of a catalyst, a mixture containing 2,5-furandicarboxaldehyde and a solvent reacts in an oxidizing atmosphere to obtain a reaction product containing 2,5-furandicarboxylic acid; The catalyst comprises a carrier and an active component; the mass percentages of the carrier and the active component in the catalyst are respectively: 85% to 95% of the carrier and 5% to 15% of the active component.
2. The synthesis method according to claim 1, characterized in that The carrier is at least one of activated carbon, alumina, and 4A molecular sieve; And / or, the active component is at least one of cobalt, copper, ruthenium and iron.
3. The synthesis method according to claim 1 or 2, characterized in that The solvent is at least one of water and a mixture of methanol and water; preferably, the volume ratio of methanol to water in the mixture of methanol and water is (1:5) to (1:10).
4. The synthesis method according to claim 1 or 2, characterized in that The oxidizing atmosphere is air or oxygen; And / or, the mass ratio of 2,5-furandicarboxaldehyde to the catalyst is (1-6): (0.1-0.3); And / or, the ratio of the 2,5-furandicarboxaldehyde to the solvent is (1-6) mol:1L.
5. The synthesis method according to claim 1 or 2, characterized in that: The reaction conditions include: reaction temperature of 60° C. to 90° C., and reaction time of 3 h to 6 h.
6. The synthesis method according to claim 1 or 2, characterized in that: The synthesis method further comprises the step of filtering the reaction product.
7. The synthesis method according to claim 1 or 2, characterized in that: The preparation method of the catalyst comprises the step of using a carrier to load the active component; preferably, when using a carrier to load the active component, a metal salt solution of the active component is mixed with the carrier, dried, and then calcined in an inactive atmosphere to obtain the catalyst; And / or, the specific surface area of the catalyst is 300m 3 / g~500m 3 / g, particle size is 40μm~90μm.
8. The synthesis method according to claim 7, characterized in that The mass ratio of the metal salt of the active component to the carrier in the metal salt solution of the active component is (3-20): (20-25); And / or, the mass concentration of the metal salt solution of the active component is 10% to 20%; preferably, the metal salt solution of the active component is at least one of copper nitrate solution, iron nitrate solution, ruthenium nitrate solution and cobalt nitrate solution.
9. The synthesis method according to claim 7 or 8, characterized in that: The mixing conditions include: a stirring rate of 500 r / min to 700 r / min, a mixing time of 1 h to 3 h, and a mixing temperature of 20° C. to 30° C.; And / or, the drying conditions include: temperature of 110°C to 150°C, time of 2h to 3h; And / or, the inert atmosphere is at least one of nitrogen and argon; And / or, the calcination conditions include: temperature of 250°C to 400°C and time of 4h to 5h; And / or, after the mixing, a step of settling is further included; preferably, the settling time is 1-3 hours.
10. 2,5-Furandicarboxylic acid obtained by the synthesis method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Catalysts and methods for the production of 2,5-furandicarboxylic acid from hydroxymethylfurfural in water
CN106795130B
Method for preparing 2,5-furyldiformate
CN104177319A
Catalyst and preparation method of 2,5-furandicarboxylic acid
CN111036195A
Preparation method of 2,5-furandicarboxylic acid
CN111039906A
Method for producing furandicarboxylic acid (FDCA)
JP2007261986A